2012
DOI: 10.1111/jpi.12006
|View full text |Cite
|
Sign up to set email alerts
|

Highly selective inhibition of butyrylcholinesterase by a novel melatonin–tacrine heterodimers

Abstract: Novel inhibitors of cholinesterases, especially butyrylcholinesterase (BuChE), were obtained by coupling melatonin-tacrine heterodimers via the carbamate bond. Compounds 14a-i possessed potent cholinesterase inhibitory activity (with IC50 values as low as 1.18 nM for acetylcholinesterase (AChE) and 0.24 nM for butyrylcholinesterase (BuChE)). These heterodimers exhibit selectivity toward BuChE, being from 4- to 256-fold more active toward BuChE than AChE, but still acting as better AChE inhibitors than tacrine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 31 publications
0
19
0
Order By: Relevance
“…Zawadzka et al. report melatonin–tacrine heterodimers (Figure ) as selective inhibitors of BuChE . The heterodimers show 4‐ to 256‐fold higher activity toward BuChE than AChE.…”
Section: Discussionmentioning
confidence: 99%
“…Zawadzka et al. report melatonin–tacrine heterodimers (Figure ) as selective inhibitors of BuChE . The heterodimers show 4‐ to 256‐fold higher activity toward BuChE than AChE.…”
Section: Discussionmentioning
confidence: 99%
“…Carbamate inhibitors bind to the active site of both cholinesterases like organophosphorus inhibitors; however, the covalent bound is not stable and the carbamate moiety is hydrolytically split from the active site after some time [29,53,54]. The mechanism of carbamate binding is sometimes called pseudo-irreversible because of carbamate moiety spontaneous hydrolysis and resurrection of cholinesterase activity.…”
Section: Division Of Inhibitorsmentioning
confidence: 99%
“…(See the next chapter). Tacrine (1,2,3,4-tetrahydroacridin-9-amine) is another synthetic drug which easily crosses the blood brain barrier and is used as a highly effective drug for ameliorating Alzheimer disease manifestation by inhibition AChE and by lower but still effective inhibition of BChE [53,66,67]. It was withdrawn from clinical use because of adverse effects.…”
Section: Division Of Inhibitorsmentioning
confidence: 99%
“…Melatonin‐derived building block 15 was obtained according to a previously developed procedure from N ‐acetylserotonin and 4‐nitrophenyl chloroformate, in the presence of N ‐methylmorpholine . N ‐Benzyl piperidine derivatives 10 and 11 are commercially available.…”
Section: Resultsmentioning
confidence: 99%
“…The first compounds of this class connect a melatonin‐derived moiety through an amide bond, using the aliphatic tail of the melatonin fragment (Figure a) . Previously, we demonstrated that the modification of the linker to a carbamate bond connected to the aromatic system of the melatonin moiety generates an excellent selectivity toward BChE (Figure b) …”
Section: Introductionmentioning
confidence: 99%